Mazarin's quest : the Congress of Westphalia and the coming of the Fronde - Sonnino, Paul (Harvard University Press, 2008)
Sonnino examines the diplomatic negotiations that took place in Westphalia from 1643 to 1648, which brought an end to the agonizing civil and religious conflict of the Thirty Years' War.